Epistemic struggles in addiction therapeutic community meetings - Pino, Marco (John Benjamins, 2014)
In this study I analyse Therapeutic Community (TC) group meetings for persons with drug addiction problems. Using the method of Conversation Analysis, I specifically focus on practices of knowledge management and sharing between the educators and clients of a TC in Italy. As part of their institutional remit, the educators encourage the clients to report information on their activities and to disclose aspects of their inner experience. This can lead to epistemic struggles, in which the clients resist providing information and the educators seek to overcome such resistance by making claims of pre-existing knowledge about the clients’ experience. After describing the design and sequential positioning of such claims, I argue that their use is functional to manage one of the dilemmas that characterise the educators’ professional practice.